Investigating the combined role of the structural vulnerability and site effects on the seismic response of a URM school hit by the Central Italy 2016 earthquake. (June 2022) - Cattari, Serena; Angiolilli, Michele; Alfano, Sara; Brunelli, Andrea; De Silva, Filomena
Abstract: The paper focuses on an emblematic case study, consisting of an unreinforced stone masonry school damaged after the Central Italy 2016 earthquakes. The proposed case study is interesting since it suffered very significant damage, as compared to the neighbouring historic centre buildings, thus questioning the role that site effect and structural vulnerability played in its structural response. A full-field survey conducted by some of the authors, as well as comprehensive geotechnical/geophysical investigations based on available microzonation studies, resulted in very accurate documentation of the occurred damage and the subsoil for the case study. Conversely, uncertainties on masonry mechanical properties, the effectiveness of constructive details and seismic input resulted in the need for the execution of parametric analyses to understand their effect on the seismic response exhibited by the building. Nonlinear dynamic analyses were carried out on the 3D building model, idealized through the equivalent frame approach. An original procedure that identifies the best matching in terms of grade and localization of the actual damage level of the building after seismic events was adopted to validate the model and confirm or deny some modelling choice assumptions. The results showed that the structure was strongly affected by the combined role of the structural vulnerability and site effects. Moreover, the outcomes of the model calibration highlighted the importance of assuming, for the examined case study, drift thresholds lower than those usually suggested in Codes, to take into account the very brittle behaviour of its poor masonry. This is also in line with recent experimental results that already suggest a possible differentiation for post-peak thresholds of the constitutive model as a function of the masonry type.